2004
DOI: 10.1098/rstb.2004.1516
|View full text |Cite
|
Sign up to set email alerts
|

Successful ageing: from cell to self

Abstract: Many people see ageing as a time of cognitive and physical decline. For the past three decades, most scientists and the general public have accepted this negative age-stereotype as the norm, but fortunately this view is now challenged. New findings show that well-being and a positive view of ageing are major protective factors against the effects of age on the organism. These results challenge the scientific studies that place emphasis on the negative side of ageing. This ageism view has been observed in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 106 publications
1
50
0
2
Order By: Relevance
“…High concentrations of cortisol and corticosterone, interpreted as hypercorticism, are frequently reported in aged humans and rats, particularly when determined in blood samples collected during the active period [10, 22]. In the present study, we found corticosterone to be highest for the 9-month-old and lowest for the 16-month-old mice during the light, inactive period with no differences in total AUC corticosterone over the dark, active period.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…High concentrations of cortisol and corticosterone, interpreted as hypercorticism, are frequently reported in aged humans and rats, particularly when determined in blood samples collected during the active period [10, 22]. In the present study, we found corticosterone to be highest for the 9-month-old and lowest for the 16-month-old mice during the light, inactive period with no differences in total AUC corticosterone over the dark, active period.…”
Section: Discussionsupporting
confidence: 61%
“…Adequate corticosteroid production is associated with successful aging in rats and humans [10, 17], while excessive corticosteroids impair mental and physical health [11]. In contrast to the reports on age-dependent hypercorticism, numerous studies indicate an apparent reduction in the sensitivity of the adrenals to ACTH stimulation, concomitant with ‘normocorticism’ [13, 17, 26, 27].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Such inquiry responds to the growing interest in factors that prevent or delay functional declines in the elderly (14,15) and to the call for integrative studies that combine influences on health across multiple domains (psychological, social, behavioral, and biological) (16). We tested these relationships by using self-reported and objective sleep assessments.…”
mentioning
confidence: 99%
“…In addition, progressive loss of sleep quality and complaints about poor sleep and fatigue are common in the elderly (9)(10)(11), and poor sleep quality increases the risk of mortality (12). Low sleep quality has also been linked to elevated IL-6 levels in patients with clinical sleep disorders (13) and experimental studies involving healthy volunteers (14)(15)(16). Social relationships, in addition, have been linked with sleep quality.…”
mentioning
confidence: 99%